Sustainability assessment in a geographical region and of the activities performed - (:unkn) unknown (IGI Global, 2016)
The applicability of emergy analysis (EA), a nature oriented thermodynamic analysis technique, as a regional sustainability assessment tool is explored in the context of an Indian village (Rampura). EA provides information about how much environmental support is required, system renewability, system efficiency, load of system to environment and dependency of system on external resources (self-sufficiency). The results of Rampura analysis reveal that sustainability is achieved neither at village level nor at subsystem levels. The chapter shows that the effective use of the renewable local resources can reduce the dependence on external resources and increase self-sufficiency and sustainability. © 2016 by IGI Global. All rights reserved.